The Potential of Ancient Sicilian Tetraploid Wheat in High-Quality Pasta Production: Rheological, Technological, Biochemical, and Sensory Insights - Rosalia Sanfilippo; Nicolina Timpanaro; Michele Canale; Salvatore Moscaritolo; Margherita Amenta; Maria Allegra; Martina Papa; Alfio Spina (Foods, 2025)
This study evaluated the potential of three ancient Sicilian tetraploid wheat genotypes—‘Margherito’, ‘Perciasacchi’, and ‘Russello’—for organic pasta production, compared to the national variety ‘Cappelli’. Significant variations in particle size distribution were found, with ‘Russello’ exhibiting the highest proportion of fine particles and the greatest protein content (14.30% d.m.). ‘Perciasacchi’ displayed the highest gluten index (81.26%). ‘Margherito’ and ‘Cappelli’ had the highest antioxidant activity, with ‘Margherito’ showing elevated levels of lutein and total carotenoids. Rheological analysis revealed differences in dough properties. ‘Perciasacchi’ exhibited the highest dough stability and P/L ratio (6.57), whereas ‘Russello’ showed the lowest values for both. Additionally, ‘Russello’ had lower consistency (12 B.U.), reduced gel stability, and limited water retention in the visco-amylographic analysis. Pasta quality was evaluated based on cooking time, water absorption, and texture. Cooking time ranged from 10 to 12 min, with ‘Russello’ and ‘Margherito’ showing lower water absorption. Texture analysis indicated that ‘Margherito’ pasta was the least firm, while ‘Russello’ showed the greatest loss of consistency when overcooked. From a sensory perspective, ‘Russello’ had lower firmness, but a stronger semolina flavor and surface roughness. ‘Cappelli’ had the most intense cooked pasta odor, while ‘Perciasacchi’ was the hardest and least sticky, though less flavorful. The results support the use of ancient tetraploid wheat genotypes as valuable resources for sustainable, high-quality pasta production.